Narrativas de formação continuada de professores de educação física: Programa Residência Pedagógica - Becker, Eriques Piccolo (2020)
Currently, being a teacher is a daily challenge. Understanding the particularities of each school, each region and each student is a teacher's need for better teaching performance and, recognizing the obstacles faced by the teaching class. This work, developed between the years 2018 and 2020, within the line of socio-cultural studies of Physical Education, present in the Master's course in Physical Education at the Federal University of Santa Maria, seeks to give teachers back the protagonism of their practice, through narratives of Continuing Education (CE) that happen from the Pedagogical Residency Program ( PRP). How the teacher puts himself in the CE process and how the possible knowledge produced by the exchange of experiences and experiences provided by the PRP are used in his pedagogical practice are some of the objectives of this study. With a qualitative approach and with the help of field diaries, built from weekly observations, and semi-structured interviews, the research proposed to perform a content analysis and interpretation after data collection. As results obtained, it is perceived the understanding, on the part of the collaborating teachers, of the PRP as a space of CE that allows moments of reflection, debate and construction of new pedagogical possibilities. In addition, the constant exchange of knowledge and experiences among PRP participants is an important link that enables qualification of Initial Training (residents) and CE (teachers). With this, the narratives presented by the collaborating teachers demonstrate an impact on their pedagogical practice caused by the PRP, in the sense that after their participation in the program, each teacher, in a different way, changed as a teacher, discovering new paths for their practice, as well as (re) discovering senses and meanings for their performance. We conclude that the PRP, when prioritizing discussions about the school context, taking into account the reality of teachers, provides a rich space for CE where teachers are the main agents of that moment. Understanding CE from the perspective of teachers is essential for future studies of this theme consider them, the true protagonists of their practice, and with that, occupy a prominent place in their continuous training process.